2006
DOI: 10.1300/j383v03n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cataloging Electronic Journals in Health Sciences Libraries

Abstract: This article reviews how electronic journals are cataloged and displayed for users of health science libraries. The Web pages of 138 health sciences libraries in the United States and Canada were examined to determine if the library provided users with a Web-based electronic journals list and whether the library used single or multiple bibliographic records to catalog print and electronic journal versions. Trends in cataloging, naming, organizing, and presenting electronic journals are identified, and summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Their research found that in most of the sample libraries, users had to search both the online catalog and a web-based list to learn all of an institution's e-journal holdings. 6 Libraries cataloging e-journals have turned to vendor records to enhance their catalogs' holdings. O'Hara noted that catalog records for e-journals are widely available from publishers, aggregators, and commercial services, and that has made it easier for libraries to include these records in their catalogs.…”
Section: Library Surveys and Practices: Electronic Journalsmentioning
confidence: 99%
“…Their research found that in most of the sample libraries, users had to search both the online catalog and a web-based list to learn all of an institution's e-journal holdings. 6 Libraries cataloging e-journals have turned to vendor records to enhance their catalogs' holdings. O'Hara noted that catalog records for e-journals are widely available from publishers, aggregators, and commercial services, and that has made it easier for libraries to include these records in their catalogs.…”
Section: Library Surveys and Practices: Electronic Journalsmentioning
confidence: 99%
“…2 Collaboration is needed to create more time for conducting usability studies, evaluation, and others kinds of research that will lead the library community to discover better ways to improve functionality of systems for users.…”
Section: Recommendationsmentioning
confidence: 99%
“…1 Likewise, a lack of standards and utilization of hybrid approaches where a web page or web list and online catalogs are maintained was highlighted and discussed by Cuddy and Bahr in 2006. 2 Librarians at the Claude Moore Health Sciences Library (CMHSL) were motivated and committed to design web pages to increase efficiency in finding critical journal information seamlessly from the library's website.…”
Section: Introductionmentioning
confidence: 99%